2002
DOI: 10.1016/s0924-9338(02)00681-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem, social adjustment and suicidality in affective disorders

Abstract: Summary -Self-esteem (SE) and social adjustment (SA) are often impaired during the course of affective disorders; this impairment is associated with suicidal behaviour. The aim of the present study was to investigate SE and SA in unipolar or bipolar patients in relation to demographic and clinical characteristics, especially the presence of suicidality (ideation and/or attempt). Forty-four patients, 28 bipolar and 16 unipolar, in remission for at least 3 months, and 50 healthy individuals were examined through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…In line with previous studies that used the Rosenberg Self-Esteem Scale [4,5,6,7,8], we found decreased self-esteem in individuals with remitted MDD which was negatively correlated with their self-contempt bias, such that the greater the self-contempt bias, the lower the self-esteem. This is in accordance with the hypothesis of Weiner [58] that attributions to stable and uncontrollable traits are particularly maladaptive for the individual.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies that used the Rosenberg Self-Esteem Scale [4,5,6,7,8], we found decreased self-esteem in individuals with remitted MDD which was negatively correlated with their self-contempt bias, such that the greater the self-contempt bias, the lower the self-esteem. This is in accordance with the hypothesis of Weiner [58] that attributions to stable and uncontrollable traits are particularly maladaptive for the individual.…”
Section: Discussionsupporting
confidence: 92%
“…Most consistently, self-blame manifests itself as the experience of worthlessness [2] in symptomatic major depressive disorder (MDD) [1,3] and reduced self-esteem after remission [4,5,6,7,8]. One hypothesis is that vulnerability to MDD is linked to proneness to experience negative emotions in general (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…First, studies have found that person with remitted bipolar disorder do not display lower self-esteem (Ashworth et al 1985; Bentall and Thompson 1990; Daskalopoulou et al 2002; Scott et al 2000; Tracy et al 1992; Winters and Neale 1985; Wolf and Mueller-Oerlinghausen 2002), more negative self-beliefs (Hollon et al 1986), or dysfunctional attitudes (Tracy et al 1992), compared with persons who have no mood disorder. Other studies found that negative cognitive styles fail to predict manic symptoms (Johnson and Fingerhut 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Low self-esteem has been associated with an adverse course of psychiatric disorders, including chronicity in major depression (Ezqueiuga et al 1999), earlier relapse in seasonal affective symptoms (McCarthy, Tarrier, and Gregg 2002), and suicidality in affective disorders (Daskalopoulou et al 2002). Higher levels of self-esteem prior to bone marrow transplantation (Broers et al 1998) and the experience of a stroke (Chang and Mackenzie 1998) precede more benign outcomes of these phenomena (Mann et al 2004).…”
Section: Self-referent Constructs and Health Statusmentioning
confidence: 99%